2023
DOI: 10.1038/s41467-023-37767-4
|View full text |Cite
|
Sign up to set email alerts
|

Increasing deep-water overflow from the Pacific into the South China Sea revealed by mooring observations

Abstract: Cold and dense water from the North Pacific Ocean that spills through the Luzon Strait, the only deep conduit between the South China Sea (SCS) and the Pacific Ocean, renews deep-water mass, modulates hydrographic and biogeochemical cycles, and drives abyssal and overturning circulations in the SCS. The variability of this key oceanic process, however, has been poorly studied, mainly due to a lack of sustained observations. A comprehensive observational program that started in 2009 has provided 12 years of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Our analyses showed that the monthly overflow transport variability from ECCO, including the seasonal cycle, is highly consistent with observations from Zhou et al. (2023) in overlap period from October 2009 to December 2017. The correlation coefficient for monthly variability is about 0.6 with p ‐value less than 0.01.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…Our analyses showed that the monthly overflow transport variability from ECCO, including the seasonal cycle, is highly consistent with observations from Zhou et al. (2023) in overlap period from October 2009 to December 2017. The correlation coefficient for monthly variability is about 0.6 with p ‐value less than 0.01.…”
Section: Methodssupporting
confidence: 92%
“…Wang, 1986;Yang et al, 2010;Zhao et al, 2014Zhao et al, , 2016Zhou et al, 2014). In a more recent study, Zhou et al (2023) analyzed observations from two deep mooring sites within Luzon Strait and estimated that the mean transport between 2009 and 2021 is about 0.84 Sv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…∆OBP contains barotropic components associated with sea level differences in the upper layer and baroclinic components related to cross‐strait density differences in the lower layer. Previous studies have confirmed that both the barotropic and baroclinic components of pressure contribute to the variability of the deep‐layer LST (Cai et al., 2023; Song, 2006; Zhou et al., 2023; Zhu, Sun, Wei, et al., 2017; Zhu, Yao, et al., 2022). The detrending ∆SLA between the two sides of the Luzon Strait moderately correlates ( r = 0.48) with the ∆OBP, implying remote modulation from upper‐layer processes.…”
Section: Discussionmentioning
confidence: 74%
“…The Luzon Strait is the only deep conduit between the Pacific Ocean and the South China Sea (SCS). Owing to the difference in pressure between the Pacific Ocean and SCS (Qu et al., 2006), exchange flows through the Luzon Strait play a key role in transporting salt, heat, and biogenic elements (e.g., nutrients and carbon) between these two regions, which greatly impacts local and global ocean circulation and biogeochemical cycles (Du et al., 2013; Liu et al., 2020; Nan et al., 2015; Wang et al., 2017; Wu et al., 2018; Xu et al., 2018; Zhou et al., 2023; Zhu et al., 2022). In the upper layer (0–200 m), the intrusion of the warmer and saltier Kuroshio into the SCS from the Pacific Ocean can form an ocean front in the Luzon Strait, which significantly impacts the local marine ecology (Guo et al., 2017; Lévy et al., 2018).…”
Section: Introductionmentioning
confidence: 99%